A Dél-Dunántúl nemzetközi versenyképességének előfeltétele: a technológiai megújulás - Horváth, Gyula (Tér és Társadalom, 1994)
The development leve] of the South Transdanubian economy was affected by – besides the economic structure, company structure, control-subordinate organisational relationships – the innovative potential of the region, the technological state and quality of the production-distribution-selling process. The industríalisation that had taken place relatively late amounted to the dependant status of the region on outside factors. Although, following the transition of company structures and ownership patterns the number of inner economic actors increased, the production- and product development – due to the lack of traditions – still has a low levei, the new economic actors usually follow the productive culture of their "predecessors". The conditions of the change of products and technology in the region are unfavourable. The changes experienced in the past three or four years show the danger of the formation of a newtype dependence between the capital and the region: the "filter" model still functions, the central region – using its localisational advantages filters the most precious productive activities – research and development, financial services, higher education, building international markets etc. – and diverts the traditional, less profitable productive branches to the peripheries. For the economy of South Transdanubia – although it might mean short-term advantages in the development of the backward regions – this solution cannot be a strategic trend, since it would inevitably preserve the structure of the region that already shows strong peripheral features. South Transdanubia will be able to modernise its structure, increase the number of the employed and improve their incomes through the strengthening of its economic autonomy, only. Seeing the unfavourable picture of the innovation potential we can state that in the development strategy of the region the experience of the developed countries have to be utilised in the formation of alI the factors of product- and technological development and also of the relationships of these factors. The author claims the opportunities of R&D, the development of technological transfer-systems. He also makes a suggestion for the development of the regional support system of the Hungarian technological policy and he defines the forms of the inner regional incentives.